If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(2x + -8) = 17 Reorder the terms: 5 + -1(-8 + 2x) = 17 5 + (-8 * -1 + 2x * -1) = 17 5 + (8 + -2x) = 17 Combine like terms: 5 + 8 = 13 13 + -2x = 17 Solving 13 + -2x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -2x = 17 + -13 Combine like terms: 13 + -13 = 0 0 + -2x = 17 + -13 -2x = 17 + -13 Combine like terms: 17 + -13 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| -4(2y)+11y=15 | | -8(v+2)+4v+5=8v+8 | | 98x^2=40 | | 4/10000 | | -4(2y)= | | y=(100+.8y)+200+100 | | y+b=16 | | 2(5r-6)-3(3r-2)-14r= | | 7[6-(-6x-4)]=294x+238 | | v/4-12.4=-11.8 | | x-6/8=3 | | (6t+5)(2t-1)= | | (2/5)x-7=(-3/5)x+8 | | 3d-8.1=6.33 | | 8.68=2s-11.1 | | 24-4x=2x-18 | | a(2b+3c)= | | 6v^2-23+10=0 | | -6x-12=6x+8 | | -4z(z-7)=0 | | -4(3-7x)= | | 6+2y=12.2 | | -6x-12=3x+8 | | 3y-2=2.26 | | 3(x+5)-2x+12= | | 7(314)-75(21)-2(259)=x(10+5) | | -2.22=m/4-5 | | 3[z-(6z+15)+5]=3(z+2) | | 1.3+2.3=2.3-2.3 | | Y+6+y=28 | | 7(314)-75(21)-2(259)=x(3+5) | | 1.2=4s-11.2 |